DEFINITION OF THE OPTIMAL APPROACH FOR RESOLUTION OF THE PROBLEMS REGARDING THE STATE POLICY IMPLEMENTATION (IN THE FRAMEWORK OF PUBLIC ADMINISTRATION REFORM IMPLEMENTATION) - Shcherbak, Natalia (Pressing Problems of Public Administration, 2021)
The article provides a deep analysis of the issues related to the definition of the optimal approach for resolution of the problems regarding the State policy implementation. It is justified that this issue becomes extremely important in the framework of the public administration reform implementation. The notion “ benefits and costs analysis” is defined as a method of decisions’ evaluation on the policy level which expresses the value of the policy results (in the monetary dimension) for all members of the society. It is underlined that the benefits and costs analysis is used today in the process of the development of the political decisions, programs, normative and legal acts as well as in the realization of other State policy activities. It is note that there are two types of the benefits and costs analysis: ex ante (which is used in the preparatory stage of a political decision) as well as ex post (after implementation of a project and a political decision). It is highlighted the issues regarding appearance and further evolution of these tools in Ukraine and other countries. It is noted that monitoring allows to describe the correlation (ratio) between the policy actions and the policy results that represent primary data source for policy implementation. It is explained that the system of monitoring and impact analysis of the State policy should have the feedback with the issues regarding realization and reform of the legislation. Considering the above-mentioned, it is underlined that the legislative initiative subjects should include in the new bills the provisions which determine the feedback procedures. On the basis of the conducted research, it is presented the practical recommendations regarding further implementation of the new innovative tools of the policy analysis in the activity of the State bodies, in particular in taking into account the main objectives of the public administration reform.